An in vitro investigation into the protective and genotoxic effects of myricetin bulk and nano forms in lymphocytes of MGUS patients and healthy individuals. (1st July 2020) - Akhtar, Shabana; Najafzadeh, Mojgan; Isreb, Mohammad; Newton, Lisa; Gopalan, Rajendran C.; Anderson, Diana
Highlights: Myricetin bulk (10 μM) and nano (20 μM) did not induce DNA damage in the lymphocytes. Lymphocytes were taken from healthy individuals and MGUS patients. Myricetin nano inhibited MNi induction in MoNc cells of patients. P53, was significantly up-regulated by myricetin at mRNA and protein levels. Abstract: The present study investigated the genoprotective and genotoxic effects of myricetin bulk (10 μM) and nano forms (20 μM) in the lymphocytes from pre-cancerous, monoclonal gammopathy of unknown significance (MGUS) patients and healthy individuals using the Comet and micronucleus assays. The study also evaluated the effect of myricetin on P53 expression levels, using the Western blot technique. Results showed that throughout the in-vitro treatment, lymphocytes from the patients group had higher levels of baseline DNA damage compared to the healthy group. Myricetin in both forms induced significant DNA damage, only at higher concentrations (>40 μM). The micronucleus assay showed a significant reduction (P < 0.01) in the frequency of micronuclei in mono-nucleated cells in the patient group treated with the nano form of myricetin at the non-toxic dose of 20 μM. There was a significant increase in both gene and protein P53 levels in lymphocytes isolated from healthy individuals and pre-cancerous patients. These results suggested a protective effect of myricetin and indicated its nutritional supplement potential for protection against cancer development among patients suffering from MGUS.